Tuberculosis Prevalence and Predictors Among Health Care-Seeking People Screened for Cough of Any Duration in Ethiopia: A Multicenter Cross-Sectional Study - Hussen Mohammed; Hussen Mohammed; Lemessa Oljira; Kedir Teji Roba; Esther Ngadaya; Tsegahun Manyazewal; Tigest Ajeme; Nicholaus P. Mnyambwa; Abebaw Fekadu; Abebaw Fekadu; Getnet Yimer; Getnet Yimer (Frontiers Media S.A., 2022)
BackgroundTuberculosis (TB) remains a major cause of morbidity and mortality in sub-Saharan Africa. This high burden is mainly attributed to low case detection and delayed diagnosis. We aimed to determine the prevalence and predictors of TB among health care-seeking people screened for cough of any duration in Ethiopia.MethodsIn this multicenter cross-sectional study, we screened 195,713 (81.2%) for cough of any duration. We recruited a sample of 1,853 presumptive TB (PTB) cases and assigned them into three groups: group I with cough ≥2 weeks, group II with cough of <2 weeks, and group III pregnant women, patients on antiretroviral therapy, and patients with diabetes. The first two groups underwent chest radiograph (CXR) followed by sputum Xpert MTB/RIF assay or smear microscopy. The third group was exempted from CXR but underwent sputum Xpert MTB/RIF assay or smear microscopy. TB prevalence was calculated across the groups and TB predictors were analyzed using modified Poisson regression to compute adjusted prevalence ratio (aPR) with a 95% confidence interval (CI).ResultsThe overall prevalence of PTB was 16.7% (309/1853). Of the positive cases, 81.2% (251/309) were in group I (cough ≥2 weeks), 14.2% (44/309) in group II (cough of <2), and 4.5% (14/309) in group III (CXR exempted). PTB predictors were age group of 25-34 [aPR = 2.0 (95% CI 1.3-2.8)], history of weight loss [aPR = 1.2 (95% CI 1.1-1.3)], and TB suggestive CXRs [aPR = 41.1 (95% CI 23.2-72.8)].ConclusionThe prevalence of confirmed PTB among routine outpatients was high, and this included those with a low duration of cough who can serve as a source of infection. Screening all patients at outpatient departments who passively report any cough irrespective of duration is important to increase TB case finding and reduce TB transmission and mortality.